A study of vowel nasalization using instantaneous spectra. (September 2021) - Prasad, RaviShankar; B, Yegnanarayana
Highlights: Study of the dynamic nature of vowel nasalization to identify duration and extent. Coupling of oral–nasal tract captured using the transition in dominant resonances of the instantaneous spectra. Partial extent of nasalization leads to a shift in dominance from oral resonance to the nasal resonance during glottal open phase. A larger extent results in a stronger nasal resonance across the full glottal cycle duration. Abstract: Nasalization of vowels is a phenomenon where the oral and nasal tracts participate simultaneously in the production of speech. Acoustic coupling of the oral and nasal tracts, together with the glottal activity, results in a complex dynamic production system. The extent of coupling determines the degree of nasalization in vowels. Changes in the instantaneous response of the vocal tract system are used to study the effects of co-articulatory load of nasals on vowels. Dominant resonance frequency (DRF) contour is extracted from the instantaneous response of the system to determine the duration of the vowel nasalization. The extent of coupling determines the relative dominance of the oral and nasal resonances during the open and closed phases of a glottal cycle. Larger coupling leads to more decay of the energy of the oral resonances, and hence the vowel spectra exhibit predominantly the nasal resonances characteristics. Comparison with the existing measures show the effectiveness of the proposed measures for determining vowel nasalization. Segments of vowels in the context of nasal consonants from utterances of both male and female speakers of English are used to illustrate different aspects of this study on vowel nasalization.